Effect of chitosan on quality and shelf life of beef at refrigerated storage - Alam, J; Murshed, HM; Rahman, SME; Oh, DH (Bangladesh Journal of Animal Science, 2018)
In this study, the microbiological quality and shelf life of beef treated with different concentrations of chitosan (CHI) was investigated. Beef samples obtained from a local market were dipped into 1%, 1.5% and 2% chitosan solutions prepared with 1% acetic acid. The samples were drained, vacuum packed and stored at 4°C for a period of 12 days. The samples were evaluated for sensorial properties (color, odor and overall acceptability) and microbial counts (TVC, TCC and TYMC) on 0, 4, 8 and 12 days of storage. Chitosan treated samples having 1%, 1.5%, 2% chitosan solution and control which were expressed as T1, T2, T3 and T0 respectively. The obtained results showed that addition of chitosan solution, significantly (p<0.05) affected on physicochemical (pH, CP, POV, Cooking Loss), microbiological (TVC, TCC, TYMC) and sensory attributes (color, odor, overall acceptance) compared to control samples at refrigerated temperature. The pH and POV of all the treatment groups increase significantly (p<0.05) compared to control group at different days of interval during storage. The CP and cooking loss of different treatment groups decrease significantly (p<0.05) compared to control group at different days of interval during storage. The results also revealed that the samples were dipped in chitosan solution (1%, 1.5%, 2%) significantly (p<0.05) improved the microbiological quality, sensory attributes and reduced lipid oxidation in beef samples compared to the control samples at different days interval. However, abnormal changes were not determined on the samples treated with chitosan, even on the last day of storage. In beef, storage at 4°C for 12 days, chitosan inhibited the growth of spoilage bacteria, reduce lipid oxidation, putrefaction and resulted in better sensory test. The results indicated that the application of chitosan on the beef samples improve the microbiological quality and extends the shelf life usually 5-8 days, which could an alternative to chemical protective additives. Bang. J. Anim. Sci. 2017. 46 (4): 230-238